Characterizing (un)binding mechanism of USP7 inhibitors to unravel the cause of enhanced binding potencies at allosteric checkpoint. (13th August 2022) - Srivastava, Mitul; Mittal, Lovika; Kumari, Anita; Agrahari, Ashish Kumar; Singh, Mrityunjay; Mathur, Rajani; Asthana, Shailendra
Abstract: The ability to predict the intricate mechanistic behavior of ligands and associated structural determinants during protein–ligand (un)binding is of great practical importance in drug discovery. Ubiquitin specific protease‐7 (USP7) is a newly emerging attractive cancer therapeutic target with bound allosteric inhibitors. However, none of the inhibitors have reached clinical trials, allowing opportunities to examine every aspect of allosteric modulation. The crystallographic insights reveal that these inhibitors have common properties such as chemical scaffolds, binding site and interaction fingerprinting. However, they still possess a broader range of binding potencies, ranging from 22 nM to 1, 300 nM. Hence, it becomes more critical to decipher the structural determinants guiding the enhanced binding potency of the inhibitors. In this regard, we elucidated the atomic‐level insights from both interacting partners, that is, protein–ligand perspective, and established the structure–activity link between USP7 inhibitors by using classical and advanced molecular dynamics simulations combined with linear interaction energy and molecular mechanics‐Poisson Boltzmann surface area. We revealed the inhibitor potency differences by examining the contributions of chemical moieties and USP7 residues, the involvement of water‐mediated interactions, and the thermodynamic landscape alterations. Additionally, the dissociation profiles aided in the establishment of a correlation between experimental potencies and structural determinants. Our study demonstrates the critical role of blocking loop 1 in allosteric inhibition and enhanced binding affinity. Comprehensively, our findings provide a constructive expansion of experimental outcomes and show the basis for varying binding potency using in‐silico approaches. We expect this atomistic approach to be useful for effective drug design.